A Leadership Model for Social Work: Drawing on Health Care to Inform Social Work Leadership. (14th October 2021) - Schaub, Jason; Hewison, Alistair; Haworth, Simon; Miller, Robin
Abstract: Leadership is a frequently used term, but these uses include various definitions and applications; these uses are sometimes contradictory. This definitional vagueness can be a particular challenge for professions, including social work. In comparison to other similar professions, there is a lack of leadership knowledge generation in social work. In addition, the organisational context in England has been challenging in recent decades, likely hindering development and application of leadership models. Health care has a broader empirical and conceptual development of leadership as a topic of examination. In health care literature, compassionate leadership is gaining momentum as a useful way of developing good clinical leadership. There is a strong tradition in social work of engaging with compassion as an element of social work values. We present models of compassionate leadership and consider their usefulness for the current social work knowledge base. We suggest that compassionate leadership may prove useful for social work practice and academia. Abstract : In this article, we examine leadership in social work. Leadership knowledge in social work is not as developed as other disciplines, such as health care. We apply a leadership model that is gaining popularity in health care, 'compassionate leadership'. Two applications of this model are presented, and we examine whether they would be useful for social work.